THE FIRST REFORMS OF THE ARABIC ALPHABET (Using the example of the work of F. Agazade and K.Karashli) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The main subject of the scientific article is writing the history of the first reforms of the Arabic alphabet, which analyses the evolution of the development of Arabic writing from a historical point of view. As a result of the study, rare information stored in libraries abroad was analysed and the history of the early reforms of the Arabic alphabet was outlined on the example of the works of F. Agazade and K. Karashli. Note that this problem under study is only the first steps of our research work, the results of which will be presented in subsequent scientific articles. In conclusion, we believe that the article contributes to the study of the first reforms of the Arabic alphabet and script, which formed the basis for the spread of Islamic culture, which is becoming one of the topical problems in Kyrgyz society.
Keywords: alphabet, Arabic letter, handwriting, Arabic writing, writing, reform, Arabic language, Kufic writing, madrasa